Application of the Value for Money Concept as a Performance Assessment Measure for Regency/City Governments in West Nusa Tenggara Province for the 2018-2022 Period - Fia Annisa Zharni; Dyah Mieta Setyawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The implementation of regional autonomy has logistical consequences in the form of the importance of effective and efficient financial management. This research aims to determine the financial performance of Regency/City goverments in West Nusa Tenggara Province for the 2018-2022 period with the concept of value for money. Value for money is a management method that is based on three elements, namely economics, efficiency and effectiveness. The object of this research is a report on the realization of the regional income and expenditure budget for the 2018-2022 period. The results of this research show that the performance of Regency/City governments in West Nusa Tenggara Province For the 2018-2022 period based on economic and efficiency ratios has had good results. On the effectiveness ratio has less good results.